INDOOR AIR POLLUTION AND THE INCIDENCE OF ACUTE RESPIRATORY INFECTION IN TODDLERS IN LATUHALAT VILLAGE, AMBON CITY, INDONESIA - Margareta Maria Sintorini; Gracia Victoria Souisa; Adriana Ritje Nendissa; Marc Ramon Julio Kesauliya (Journal of Synergy Landscape, 2025)
Acute Respiratory Infection (ARI) is a primary cause of disease burden in developing countries, ranking one among the top 10 in the Latuhalat Health Center Work Area. One of the contributing factors to its occurrence in toddlers, who spend most of their time at home, is indoor air pollution, particularly in rural areas. Therefore, this study aimed to investigate the potential correlation between indoor air pollution from cigarette smoke and the use of firewood. To achieve this, a cross-sectional design with quantitative analysis has been employed, surveying 91 respondents through a questionnaire. Data were analyzed using univariate and bivariate analysis. The results showed that there was a relationship between exposure to cigarettes and firewood smoke and the incidence of ARI among toddlers in the Latuhalat Health Center work area (p = 0.002). There is a significant relationship between exposure to cigarette smoke and firewood smoke with the incidence of ARI. The risk of toddlers getting ARI if exposed to cigarette smoke and firewood smoke is 6.2 times greater than toddlers who are not exposed to these smoke in the working area of ​​the Latuhalat Health Center.